2008
DOI: 10.1093/humrep/den414
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the threat related to the use of seminal fractions from hepatitis C virus-infected men in assisted reproductive techniques

Abstract: These results emphasize the safety of the semen-processing method. The negligible risk of transmitting HCV reduces the value of the systematic analysis of HCV RNA in seminal fractions prior to ART. Since use of this analytical procedure involves the freezing of semen, its avoidance would result in an increase in sperm quality and reduce the need to perform intracytoplasmic sperm injection techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…A number of questions are raised by our results. Consistent with previous work [ 7 , 8 , 11 ], we have found that approximately one third of HIV-infected men with HCV infection shed HCV into their semen, and that this shedding is both qualitatively (ie, detected or not detected) and quantitatively related to the magnitude of blood HCV VL; however, less-so during chronic HCV infection. Shedding in semen was not always present when the blood HCV VL was high, nor was it always absent when the blood HCV VL was low, although these were significantly correlated, with 15 (94%) of 16 of specimens with detectable HCV shedding having a paired blood VL of >5 log 10 IU/mL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A number of questions are raised by our results. Consistent with previous work [ 7 , 8 , 11 ], we have found that approximately one third of HIV-infected men with HCV infection shed HCV into their semen, and that this shedding is both qualitatively (ie, detected or not detected) and quantitatively related to the magnitude of blood HCV VL; however, less-so during chronic HCV infection. Shedding in semen was not always present when the blood HCV VL was high, nor was it always absent when the blood HCV VL was low, although these were significantly correlated, with 15 (94%) of 16 of specimens with detectable HCV shedding having a paired blood VL of >5 log 10 IU/mL.…”
Section: Discussionsupporting
confidence: 92%
“…Despite significant epidemiological [ 2 , 3 , 5 , 17 ] and virological evidence [ 7 10 ], the role of HCV in semen in the sexual transmission of HCV among HIV-infected MSM still remains controversial. The phrases “traumatic sex” or “anal trauma” are commonly cited as necessary elements of HCV acquisition, but these factors have not been found consistently [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential factors that may influence this exchange include the titer of virus, the integrity of the mucosal surfaces, and the presence of other genital infections (viral or bacterial). Studies to detect HCV RNA in semen (seminal fluid and cells), vaginal secretions, cervical smears, and saliva have yielded mixed results 14‐20. Failure to detect HCV RNA in body secretions from chronically infected subjects may be due to technical factors (e.g., specimen collection and storage) and the inability to exclude cellular components and to overcome the presence of polymerase inhibitors in body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…However, Garrido et al (11) reported that a long evolution of HCV disease did not negatively affect sperm motility. Bourlet et al (18) found that, although 20% of the semen plasma were positive for HCV in their cases, there was no change of semen parameters. Also, Vicari et al (19) showed that sperm parameters had nonsignificant correlation with the duration of either infertility or viral infection.…”
mentioning
confidence: 87%